Assessing Sustainable Environmental Awareness Among Phase C Elementary School Students in Sorong Regency - Diah Masythoh; Febrian Andi Hidayat; Solehun Solehun; Surya Putra Raharja (CV. Dharma Samakta Edukhatulistiwa, 2026)
This study aims to describe the profile of sustainable environmental awareness among Phase C students at SD Inpres 13 in Sorong Regency, covering the dimensions of knowledge, attitudes, and behavior. The study employed a descriptive survey method involving 35 students, consisting of 20 fifth-grade students and 15 sixth-grade students. Data were collected using a 15-item questionnaire covering three dimensions of sustainable environmental awareness: knowledge, attitudes, and behavior. The instrument demonstrated satisfactory content validity (CVI > 0.80) and reliability (Cronbach’s Alpha = 0.82). Data were analyzed descriptively using percentage techniques.The results showed that students’ sustainable environmental awareness was generally categorized as good, with an average percentage of 72.39%. The attitude dimension achieved the highest score (81.2%), indicating that students demonstrated positive environmental attitudes and strong concern for sustainable practices. The behavior dimension reached 69.9%, while the knowledge dimension obtained the lowest score (67.4%), particularly regarding issues related to the greenhouse effect and climate change. Descriptive analysis also showed variations in sustainable environmental awareness across grade levels and gender groups; however, these findings should be interpreted cautiously because no inferential statistical tests were conducted. Overall, the findings highlight the importance of strengthening environmental education through experience-based learning, sustainability projects, and school-wide environmental practices to support the development of environmental literacy and Education for Sustainable Development (ESD) competencies among elementary school students.